KAJIAN KEBERLANJUTAN ALIRAN DASAR SUNGAI MELALUI ANALISIS KURVA RESESI HIDROGRAF PADA DAS KEDUANG KABUPATEN WONOGIRI PROVINSI JAWA TENGAH - Bokiraiya Latuamury; Hendrik S.E. Aponno; Miranda H. Hadijah (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2017)
The streamflow hydrograph recession curve notes that behavior of the relationship between the aquifer structure and dependencies with the groundwater outflow towards river basin channel. The recession behavior of river basin hydrographs will investigate to understand the hydrology processes of the river basin in the future. This research was conducted with the aim: to analyze the characteristics of the baseflow recession based on the parameters and coefficients of the recession, and the shape of the individual recession curve and the master recession curves both manually and through the processing of genetic algorithms using a linear reservoir model of hydrooffice software package recession curve (RC) 4.0. The results of the visualization of the recession curve shape of the watershed of the research shows there is a very interesting trend in the watershed storage process.The characteristics of the baseflow recession to research watershed with the recession curve slope describe the baseflow recession conditions, especially excellent water storage. The river basin of Keduang have the form of a relatively sloping recession curves, both individual and master recession curve with relatively high recession constant ranged between 0,80 – 0,90 have baseflow recession characteristic is excellent, i.e. the watershed water storage which is the higher volume of water storage.